Difference analysis of intestinal microbiota in patients in the intensive care unit using different sampling methods: a systematic review and meta-analysis - Qiu, Songlin; Zheng, Binyang; Pan, Juan; Yu, Sufei; Qian, Jiao; Tung, Tao-Hsin; Shen, Bo (Frontiers in Microbiology, 2026)
BackgroundThe normal intestinal microbiota undergoes rapid and notable changes in patients in the intensive care unit (ICU) because of factors such as host physiological stress, changes in gastrointestinal function, and antibiotic exposure. Different specimen types are used for intestinal microbial analysis because of sampling difficulties. Therefore, this study conducted a meta-analysis to investigate changes in the intestinal microbiota of patients admitted to the ICU and whether using different specimen types affects microbiota analysis.MethodsA systematic review was conducted encompassing studies published in electronic databases up to May 1, 2024. We included 11 studies that compared the abundance and diversity of the gut microbiota between ICU patients and healthy cohorts (HC). A standardized mean difference (SMD) meta-analysis using random effects models was performed to quantify microbial differences, including an assessment of various sampling methods.ResultsAfter ICU admission, the intestinal microbiota of patients differed significantly from that of the normal population, showing lower diversity and richness. A significant difference in beta diversity was also observed. Specifically, the relative abundances of Proteobacteria and Fusobacteria were elevated in ICU patients, while Firmicutes abundance was diminished. Crucially, the comparison of stool versus rectal swab specimens demonstrated no significant difference in the measured alpha diversity of the gut microbiota.ConclusionThe early intestinal microbiota of patients in the ICU differed from that of healthy individuals. A comprehensive understanding of the early changes in the intestinal microbiota of patients in the ICU can help formulate prevention and treatment strategies. Furthermore, using feces and swab samples for analysis did not significantly affect the diversity of the intestinal microecology. Therefore, rectal swabs may be an attractive method for sampling the gut microbiota and metabolome.Systematic review registrationPROSPERO Registration number is CRD42022385146 (Available from: https://www.crd.york.ac.uk/PROSPERO/view/CRD42022385146).